Acetylation of retinoblastoma-like protein-2 (Rbl2/p130): an additional check on cell proliferation? - Saeed, Muhammad (European Journal of Oncology and Environmental Health, 2015)
Pocket proteins are important regulator of cell cycle progression. The family includes three members namely: retinoblastoma protein (pRb/p105), the founding member of the family, retinoblastoma like protein-1 (Rb121/p107) and retinoblastoma like protein-2 (Rb12/p130). Pocket proteins exert their role by binding with the members of E2F family of transcription proteins, thus making them unavailable for transcription of gene required for the entry into S-phase of cell cycle. The Functional activity of pocket proteins is regulated by phosphorylation. Once phosphorylated, Rb-E2F complex is disrupted. The abrogation of Rb functions, leads to unchecked G1-S phase transition and uncontrolled cell division. The ultimate impact is tumor formation. Recently, we have demonstrated that Rbl2/p130 is also subject to posttranslational acetylation. The exact role of Rbl2/p130 acetylation in cell cycle control and tumor genesis remains elusive. This review discusses acetylation being a prerequisite for phosphorylation and investigates a possible role of Rbl2/p130 acetylation in regulating G1/S phase of cell cycle.